1993
DOI: 10.1128/mcb.13.1.613
|View full text |Cite
|
Sign up to set email alerts
|

Profilaggrin is a major epidermal calcium-binding protein.

Abstract: Profilaggrin is a major highly phosphorylated protein component of the keratohyalin granules of mammalian epidermis. It contains 10 to 12 tandemly repeated filaggrin units and is processed into the intermediate filament-associated protein filaggrin by specific dephosphorylation and proteolysis during terminal differentiation of the epidermal cells. Later, filaggrin itself is degraded to free amino acids that participate in maintenance of epidermal flexibility. The present paper describes the structural organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(69 citation statements)
references
References 36 publications
0
67
0
2
Order By: Relevance
“…Many of the S100 genes, including S100A10 (69, 70) and S100A11 (54,71), have been co-localized on the same chromosome as other epidermal structural protein genes, suggesting a possible function in skin. Thus, the S100 proteins join another keratinocyte envelope precursor, profilaggrin, as an EF hand-containing protein (72). Trychohyalin, a hair follicle protein, which may also be an envelope precursor, also contains an EF hand that may be functionally important (73).…”
Section: Discussionmentioning
confidence: 99%
“…Many of the S100 genes, including S100A10 (69, 70) and S100A11 (54,71), have been co-localized on the same chromosome as other epidermal structural protein genes, suggesting a possible function in skin. Thus, the S100 proteins join another keratinocyte envelope precursor, profilaggrin, as an EF hand-containing protein (72). Trychohyalin, a hair follicle protein, which may also be an envelope precursor, also contains an EF hand that may be functionally important (73).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AP-1 sequences from the calcium-responsive element of the human keratin 1 gene (gaTGATTCAct) (Hu et al, 1993;Rothnagel et al, 1993), from position 777 of the 5' region of the human pro®laggrin promoter (gaTGAATCAct) (Markova et al, 1993), and from one of the AP-1 sites (gtTGACTAAcg) at position 7288 of the 5' noncoding region of the human involucrin gene (LopezBayghen et al, 1996) were also cloned as 56 multimers into the same pBLCAT2 reporter construct (Figure 3a). Supershift analysis indicated that the composition of the AP-1 complexes bound to these sequences in 0.12 mM calcium was the same (not shown).…”
Section: Tpa and Calcium Induce Ap-1 Dna Binding Activitymentioning
confidence: 99%
“…The exceptions found to date are the monomeric calbindin D 9k , which was suggested to have a calcium-buffering role (Szebenyj & Moffat, 1986), and p26olf, which is a single-chain molecule consisting of two almost identical S100-like domains (Miwa et al, 1998;Tanaka et al, 1999). In addition, two high molecular weight proteins, the intermediate ®lament-associated protein precursors pro®laggrin (Markova et al, 1993) and trichohyalin (Lee et al, 1993), contain S100-like domains. There are also exceptions in terms of calcium binding: for example, S100A10 (Re  ty et al, 1999) and the N-terminal loop of S100A7 (Brodersen et al, 1998) do not bind calcium, while S100A3 was reported to have very low af®nity for calcium (Fohr et al, 1995).…”
Section: Introductionmentioning
confidence: 99%